Os olhares de Fatumbi: o lugar da fotografia na Fundação Pierre Verger: Fatumbi's looks: the place of photography at the Pierre Verger Foundation (Revista de História da UEG (REVHIST), 2020)
This text aims to understand the place of photography in the Pierre Verger Foundation from a historical perspective. We analyzed the collection construction process, its technical treatment, its availability to the public and some of its social uses. The investigation of these points is also permeated by the appreciation of the photographer's biographical aspects and the Institution's operating and financing structure.Keywords: Pierre Verger Foundation. Photography. Bahia-Brazil.